2013
DOI: 10.1080/03036758.2013.802701
|View full text |Cite
|
Sign up to set email alerts
|

Auckland's green volcanic heart: groundcover vegetation and soils of the Auckland volcanic cone reserve network

Abstract: The volcanic cones of Auckland are distinctive landmarks of that city, currently realized as an 'archipelago' of grassy reserved hills. Most of these cones were modified as hill forts during former occupation by Māori. Here, we review the Auckland volcanic reserve network and survey the current groundcover vegetation and soils of four large representative examples. Forty-eight reserves currently occur on remnant volcanic features. As well as two inshore island reserves (2372 ha), the other 46 reserves total 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In addition, substantial human trampling occurred on some of the plots, and we suspect this also contributed to plant losses. The initial vegetation survey (Burns et al 2013) showed that Microlaena was largely absent on this topographical unit, probably due to high levels of competition from other species on high-fertility soils Esler and Esler (2010). This absence was the reason for locating Experiment II on these terrace sites, but they also presented the greatest challenge to revegetation with Microlaena, given the early results of Experiment I (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, substantial human trampling occurred on some of the plots, and we suspect this also contributed to plant losses. The initial vegetation survey (Burns et al 2013) showed that Microlaena was largely absent on this topographical unit, probably due to high levels of competition from other species on high-fertility soils Esler and Esler (2010). This absence was the reason for locating Experiment II on these terrace sites, but they also presented the greatest challenge to revegetation with Microlaena, given the early results of Experiment I (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The existing grassland cover of these cones is dominated by exotic pasture species that form a number of different community assemblages based on environmental factors such as slope, soil properties, grazing intensity and tree cover (Burns et al . ). Dominant species include Perennial Ryegrass, Kikuyu, bromes ( Bromus spp.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present day, they are mostly protected as parks and recreational spaces well utilized by inhabitants of the city. However, they offer very little geologically unique aspects mostly due to the fact that they are grass covered with no exposures preserved or readily accessible [55][56][57]. In the southern part of the city, volcanoes are typically phreatomagmatic volcanoes, and explosion craters (shallow maars) surrounded by tuff rings are common [58].…”
Section: Auckland Volcanic Fieldmentioning
confidence: 99%
“…Also, unlike Maungawhau and Maungarei cones, comprising especially high organic matter and soil nitrogen, the Maungakiekie cone has the highest P levels. While the soils in the plane and slightly gradient areas contain higher C, N and P than the gradient areas, the slopes in the north have a higher P content than the slopes in the south (Burns et al, 2013). Şenol et al (2014) investigated the elemental losses (i.e., Ca, Mg, K, Na, Si, Al and Fe) of soils in Isparta Çünür Hill containing geologically volcanic sand, limestone and andesite/trachyandesite and weathering products.…”
Section: Introductionmentioning
confidence: 99%